Implementation of PP No. 71 of 2010 concerning Accrual-Based Government Accounting Standards in the Preparation of Financial Statements - Dewi, Khadijah Dinda Putri; Siregar, Saparuddin; Nasution, Juliana (PT. Riset Press International, 2023)
This study aims to look at HR's understanding of the implementation of Accrual-Based SAP and to find out the application of accrual-based government accounting standards in Government Agencies of the North Sumatra Province Environment and Forestry Service,This study applies a descriptive qualitative approach with data collection techniques, namely observation, interviews, and documentation,Application of Government Accounting Standards to the Environment and Forestry Service of North Sumatra Province only presents 5 financial reports, namely the Budget Realization Report, Balance Sheet, Operational Report, Report on Changes in Equity and Notes to Financial Statements. It can be concluded that the financial reports presented by the Environment and Forestry Office of North Sumatra Province are in accordance with Government Regulation Number 71 of 2010.It can be concluded that the readiness of Human Resources (HR) at the Department of Environment and Forestry of North Sumatra Province is Inadequate. This is due to the lack of competent human resources in preparing financial reports and the lack of knowledge regarding the accrual basis at the North Sumatra Province Environment and Forestry Service. But it does not hinder and disrupt the process of preparing accrual-based financial reports, in which HR is guided by the preparation of financial reports in the previous period.